Development of E-Module for Writing Negotiation Texts Assisted by Flipbooks for Grade XI High School Students - Fijri Astuti, Tia; Chalina, Chalina; Mangatur Sinaga (Jurnal Onoma: Pendidikan, Bahasa, dan Sastra, 2025)
Learning to write negotiation texts is an essential skill that students must master. This research aims to develop an e-module for writing negotiation texts through flipbook media based on contextual learning and to evaluate its effectiveness on students' learning interest and outcomes in class XI of high school. The research method used is Research and Development (RnD). The sample consists of 72 students divided into two classes: an experimental class using the e-module and a control class employing conventional teaching methods. The analysis technique applied in this study refers to the ADDIE model (Analysis, Design, Development, Implementation, Evaluation). This approach ensures that each phase of the module development is conducted systematically and planned. The results of hypothesis testing indicate that the e-module for writing negotiation texts assisted by flipbook media significantly improves students' interest and learning outcomes. The average learning outcomes of students in the experimental class show much higher scores compared to the control class. The discussion reveals that the developed e-module is not only effective in enhancing students' writing skills but also successfully boosts their learning interest. Feedback from expert validation and the practicality test results support the sustainability of using the e-module as an innovative learning aid.